Big Data and the Essential Facilities Doctrine: A Law and Economics Approach to Fostering Competition and Innovation in Creative Industries - Deirdre Ryan (UCL Journal of Law and Jurisprudence, 2021)
This article examines the growing market power of global streaming services in creative industries for video and music, and the intellectual property investments and inputs in these services. The author considers the prevalence of big data in these industries, enabling the development of highly targeted content, thereby dramatically reducing the potential of failure and mitigating the cost of investment. The author examined the suitability of traditional intellectual property laws for creative works driven largely by data inputs. The possibility of utilising the essential facilities doctrine to impose a duty to licence on these undertakings and the impact that could have on competition, innovation, incentives, and the economic functioning of creative industries is explored.
Keywords: Competition Law; Intellectual Property; Antitrust; Netflix; Spotify; The Essential Facilities Doctrine; Law and Economics; Big Data; Competition Policy; Intellectual Property Rights; Data-Driven Creativity